PENERAPAN METODE WATERFALL DALAM MERANCANG APLIKASI MOBILE GURU DAN ORANG TUA - Riski Anisa; Muhammad Rivaldi Baihaqi (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
In the current development of educational technology, the world of education cannot be separated from the role of the internet. Mobile devices have become part of human daily life in facilitating activities, currently, the need for mobile-based information technology is very necessary, therefore schools need an information system that can support and provide services between teachers (schools) and parents of students. . This study discusses the application of the waterfall in designing mobile-based teacher and parent applications. Currently, most of the information systems in schools are still done manually, starting from news announcements, school grades, and tuition payments, making it possible for errors to occur during the delivery process. The design of this application is the best solution to solve problems that exist in schools, and with a computerized system, an effective and efficient activity can be achieved in supporting activities at this school.